Direct Comparison of the Structural Compression Characteristics of Natural and Synthetic Fiber-Epoxy Composites: Flax, Jute, Hemp, Glass and Carbon Fibers - Mike R. Bambach (Fibers, 2020)
Recent decades have seen substantial interest in the use of natural fibers in continuous fiber reinforced composites, such as flax, jute and hemp. Considering potential applications, it is of particular interest how natural fiber composites compare to synthetic fiber composites, such as glass and carbon, and if natural fibers can replace synthetic fibers in existing applications. Many studies have made direct comparisons between natural and synthetic fiber composites via material coupon testing; however, few studies have made such direct comparisons of full structural members. This study presents compression tests of geometrically identical structural channel sections fabricated from fiber-epoxy composites of flax, jute, hemp, glass and carbon. Glass fiber composites demonstrated superior tension material coupon properties to natural fiber composites. However, for the same fiber mass, structural compression properties of natural fiber composite channels were generally equivalent to, or in some cases superior to, glass fiber composite channels. This indicates there is substantial potential for natural fibers to replace glass fibers in structural compression members. Carbon fiber composites were far superior to all other composites, indicating little potential for replacement with natural fibers.